The effect of bull exposure on the early postpartum reproductive performance of suckling angus cows - Landaeta-Hernández, Antonio; Meléndez, Pedro; Bartolomé, Julián; Rae, Owen; Archbald, Louis (Revista Científica de la Facultad de Ciencias Veterinarias)
The present study tested the effect of biostimulation by bull exposure on the early postpartum reproductive performance of well fed and permanently suckled Angus cows. At 1 week postpartum, 90 Angus cows with no history of calving problems and their calves were allocated by parity, body weight, and body frame into 3 isolated groups of 30 cows each. Cows from groups A and B were permanently exposed to mature bulls (BE) while cows from Group C (NE) served as a control. Analyzed variables included; intervals from calving to resumption of ovarian activity (ICR), and first behavioral estrus (ICE), length of the first estrous cycle (ECL), number of cows showing estrus/group, and number of estrus periods (NEP) occurred per cow during the 90 days previous to the breeding season. The ICR (38.1 Ó 3.4 vs 51.0 Ó 4.4; P<0.02) and ICE (38.1 Ó 3.4 vs 59.9 Ó 2.5; P<0.001) were shorter in BE than in NE cows, and no differences between bull-exposed groups were found. More BE cows resumed reproductive cyclicity with normal ECL than NE cows (A= 16/53%, B=16/53%, C=8/26.6%; P<0.01). During trial, more BE cows showed behavioral estrus than NE cows (A: 29/30= 97%, B: 30/30 =100%, and C: 24/30 = 80%; P<0.002). Similarly, NEP recorded in BE cows was greater than that of NE cows (A=70, B=68, and C=42; P<0.0002). More BE cows (P< 0.001) had 3 estrous periods during trial. It was concluded that, even under conditions involving adequate nutrition and permanent suckling, there was a positive effect of biostimulation on early reproductive performance in postpartum Angus cows